Between Fear and Survival: Human Security Issues in Citarum River Basin, Indonesia - Arry Bainus (Librelloph, 2021)
This article offers an empirical finding of human security issues in Citarum River, Indonesia, which was once labelled as the dirtiest and most polluted river in the world. Using a theoretical framework based on actor-based security model, this research seeks to analyse a local community's experience in a village affected by severe environmental degradation of its river basin and its relation to other actors in security policy making process. The article explores how a local people evaluate the ongoing environmental degradation and its impacts to their life. This analysis leads to the finding that local people are aware of the threats from their environment, but at the same time they still have to depend on the economic activities that has been polluting the river. This condition makes them unable to advocate for what they experienced to the policy makers and choose to be resilient. On the other hand, the government's policies tend to ignore the perspective of the local community in formulating a security policy. This supports previous studies that the concept of human security still has little impact on addressing environmental issues, especially at policy level. <!-- p, li { white-space: pre-wrap; } -->